The Value of Legal Education in The Resolution of Marital Property Disputes by The Religious Court of Kediri City Perspective Compilation of Islamic Law (KHI)) - Nurbaedah, Nurbaedah (Didaktika Religia, 2022)
This article aims to provide legal education to the public about the resolution of common property disputes from the perspective of the Compilation of Islamic Law (KHI). More specifically, the author reviewed casuistically the rulings produced by the Kediri City Religious Court regarding the resolution of marital property disputes. This article was compiled using qualitative methods with this type of case study. Data is collected through interviews, observations, and documentation. Next, the data were analyzed with Miles-Huberman’s interactive model. This article concludes that the ruling of the Kediri City Religious Court is quite flexible and contextual. This is reflected in several cases, where on one occasion, the Kediri City Religious Court had given a ruling on the settlement of property disputes together regarding article 97 of the KHI while considering article 89 paragraph 1 of Law No. 7 the Year 1989 on Religious Justice. Then on another occasion, the Kediri City Religious Court has also ruled out article 97 of KHI as a consideration in the ruling regarding the settlement of marital property disputes because it is considered unfair based on the facts before the trial. That is, judges have the authority to position the principle of justice and contextual expediency as key in the resolution of common property disputes, which have far exceeded the normative side or formal legal aspects of the law.